2012
DOI: 10.1111/j.1524-475x.2012.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acute and long‐term pathologies of superficial and deep dermal sulfur mustard skin lesions in the hairless guinea pig model

Abstract: Sulfur mustard induces severe acute and prolonged damage to the skin and only partially effective treatments are available. We have previously validated the use of hairless guinea pigs as an experimental model for skin lesions. The present study aimed to characterize a model of a deep dermal lesion and to compare it with the previously described superficial lesion. Clinical evaluation of the lesions was conducted using reflectance colorimetry, trans-epidermal water loss and wound area measurements. Prostagland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Human skin also develops redness and edema followed by large vesicles after L or HD exposure . In animal models, microvesications represent an important criterion in developing in vivo models for the study of the vesicant exposure that we also found in the SKH‐1 mouse skin treated with L. Furthermore, our histological observations revealed degeneration of the basal cells in the epidermis associated with cell inflammatory infiltrates and edema followed by cell death. We reported that the deep wounds were totally closed within 21 days.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Human skin also develops redness and edema followed by large vesicles after L or HD exposure . In animal models, microvesications represent an important criterion in developing in vivo models for the study of the vesicant exposure that we also found in the SKH‐1 mouse skin treated with L. Furthermore, our histological observations revealed degeneration of the basal cells in the epidermis associated with cell inflammatory infiltrates and edema followed by cell death. We reported that the deep wounds were totally closed within 21 days.…”
Section: Discussionsupporting
confidence: 65%
“…7 We thus focused our study on the MMP-2 and -9 levels as no study to date has revealed the role of these two gelatinases in L-induced skin toxicity. The patterns of activity and expression of MMP-2 and -9 after HD challenge were extensively described in animal models, 11,12 including the SKH-1 mouse. 9,10,15 Our results showed preferential MMP-9 expression and activation after L challenge as previously described following HD exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several animal models including weanling pigs (Sabourin et al, 2002;Smith et al, 1996Smith et al, , 1997b, hairless guinea pig (Benson et al, 2011;Dachir et al, 2010Dachir et al, , 2012Smith et al, 1997a), rabbit (Dannenberg et al, 1985) or various mouse species (Lomash et al, 2011(Lomash et al, , 2013Powers et al, 2000;Ricketts et al, 2000;Sabourin et al, 2004;Wormser et al, 2005) have been used to investigate SMinduced skin toxicity. During the last years, the hairless mouse model stood out as the model of choice for studying the skin pathogenesis of SM Dorandeu et al, 2011;Joseph et al, 2011;Vallet et al, 2012) or its analogues the chloroethyl ethyl sulfide (CEES) (Jain et al, 2011a,b,b;Tewari-Singh et al, 2009) or the nitrogen mustard Jain et al, 2014;Tewari-Singh et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] SM is known to damage not only epidermal structures, including the basement membrane, but also stromal and vascular components of the skin tissue. [21][22][23] Translating SM data from animals to humans has been challenging not only because there is little or no blistering, but also to additional factors such as distinct structural differences in the tissue, unique aspects of the immune system, and mechanisms of wound healing. For example, in mice, the skin and epidermis are thinner when compared to humans, there are fewer epidermal cell layers, a lack of epidermal ridges and eccrine sweat glands, and limited adherence to underlying tissues.…”
mentioning
confidence: 99%